(3cTa GdNaG heRjd GdEdHGS YeG GTJgQ ef GdCMGOjK Ydi CdSfI GdfGSs - (3GdYLdhfj , ESeGYjd Hf eMeO Hf YHO GdgGOj GdLQGMj GdOeTbj, CHh GdaOGA,J (B1162 (3g` s
(3ChdgG (B:s
(3CeG HYO ajbhd GdYHO GdabjQ GSeGYjd GdYLdhGfi GHf eMeO LQGM Ef GdCMGOjK GdeTJgQI Ydi GdCdSfI bO cKQJ ajgG GdJUGfja aCQOJ Cf CdNU HeG hbaJ Ydjg efgG s
(3BNQgG (B:s
(3hQhi Yf LGHQ QVi Gddg JYGdi Yfg eQahYkG CNha eG CNGa Ydi CeJi EJHGY Gdghi hWhd GdCed aEf GJHGY Gdghi ajVd Yf GdMb hCeG Whd GdCed ajfSi GdBNQI hai GdJfRjd hdGJJHY Gdghi ajVdc Yf SHjd Gddg s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B325 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B292s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B2 - (3U (B359s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
Keywords: (3GdMOjK h GdeUWdMs